В сторону Тулы: Заметки и дополнения к новому изданию романа Андрея Николева [_Du côté de Toula_: Notes and Supplements to the New Edition of _Beyond Tula_ by Andrei Nikolev] - Zeltchenko, Vsevolod (Slavica Revalensia, 2023)
This paper aims to offer a supplement to the rich and suggestive commentary by A. Agapov, D. Bresler and Chr. Konstantinova in the recent (2022) edition of the novel Beyond Tula (1931) by Andrei Nikolev (a pseudonym of A. N. Egunov, a classical scholar, translator, and poet). The article, in its collection of remarks, identifies a number of quotations and allusions present in Nikolev’s chef-d’œuvre as well as some sources of his inspiration and features of his narrative techniques.